The force-velocity mechanical profile in sprint running: Perspectives in hamstring muscle injury follow-up and prevention - Edouard, P.; Samozino, P.; Mendiguchia, J.; Morin, J.-B. (New Studies in Athletics, 2015)
Hamstring muscle injuries - the main type of injury related to athletics and other sports involving acceleration and sprints - can have substantial negative consequences for the affected athletes. Increased knowledge of the risk factors and mechanisms of these lesions based on a better understanding of the biomechanical and muscular determinants of performance in sprinting would, of course, be of great value. Studies have reported a change in the Force-velocity profile (F-v profile) and a decrease in maximum theoretical horizontal force (FJ following hamstring injury that could be a consequence of the injury. Collection of data related to the mechanical properties of sprinting, including the F-v profile, Fho and maximum theoretical velocity (VJ, is possible in real-practice conditions using simple and easily available tools. Analysing the hamstring propulsion function in a maximum acceleration sprint looks promising and, in particular, F-v profile evaluation could be used to screen athletes at risk of hamstring muscle injury and to guide the return to maximum velocity sprinting after a hamstring muscle injury.